PEGERAKAN KELOMPOK TERORISME DIKALANGAN UMMAT ISLAM (Suatu kajian dengan pendekatan Sejarah) - St. Aisyah Abbas (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2021)
Terrorism is an ideology which argues that the use of means of violence, intimidation and the like that cause anxiety and fear, even the occurrence of loss of life and property, to achieve goals, either individually or in groups or in an organization, which has a wide network, both national and international scale. Academically, terrorism is categorized as an "extraordinary crime" and is also categorized as a "crime against humanity", which is inhumane. Terrorism has a long history and its development follows the development of human life with situations that support it, so that the more sophisticated the technology possessed by humans, the more terrorist networks and criminal acts will be able to carry out terror anywhere and anytime, and terror in today's phenomenon is changing and changing. its impact is felt by the wider community. If the terrorism movement is associated with Islamic views, Muslim scholars and scholars still have differences of opinion, especially regarding the issue of "martyrdom bombings or suicide bombings". On the other hand, if the suicide bombing is carried out in a safe area/country, then the perpetrator is not categorized as a martyr.